More on Democratic Fundamentals in Solomon Islands: Minister for Provincial Government v Guadalcanal Provincial Assembly - Brown, Kenneth; Corrin Care, Jennifer (Victoria University of Wellington Law Review, 2001)
In 1997 the High Court of Solomon Islands delivered its decision in Guadalcanal Provincial Assembly v The Speaker of National Parliament, 1 declaring void the Provincial Government Act 1996, 2 on the basis that several parts of that measure were unconstitutional. That decision was considered 3 and criticised 4 in an earlier article. The Court of Appeal allowed an appeal against that judgment. This paper examines the Court of Appeal's decision and comments on its significance for Solomon Islands and the South Pacific region generally. In particular, it considers the extent of state legislative power, the role of a preamble, and the human rights implications for women.